The strongest gravitational lenses: IV. The order statistics of the largest Einstein radii with cluster mergers - Redlich, Matthias; Waizmann, Jean-Claude; Bartelmann, Matthias (Arxiv, 2014)
Based on techniques developed in the previous papers of this series, we investigate the impact of galaxy-cluster mergers on the order statistics of the largest Einstein radii. We show that the inclusion of mergers significantly shifts the extreme value distribution of the largest Einstein radius to higher values, typically increasing the expected value by ${\sim}10%$. A comparison with current data reveals that the largest observed Einstein radius agrees excellently well with the theoretical predictions of the $Λ$CDM model at redshifts